The Impact of Race on Employment during the 2005-2011 Recession (Global Journal of Management and Business Research, 2018)
Following the recent US Recession and global financial meltdown, many Americans lost their jobs and many more queuing for jobs in the labor market significantly lost their initial prospects of being employed. Even before the onset of the financial turmoil, the labor market was still not equally receptive of persons of different colors, with the African Americans being the worst affected. The Critical Race Theory (CRT) and the Life Course Theory (LCT) are both made up of crucial tenets that were used to explain the disparities observed in awarding of job opportunities in various states across the US. The study used data collected through the Current Population Survey (CPS) administered by the US Census Bureau and the Bureau of Labor and Statistics; surveys from
Keywords: race; workforce; unemployment; employment opportunities